2007
DOI: 10.1182/blood.v110.11.1240.1240
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma Protein and the Leukemia-Associated PLZF Transcription Factor Interact To Repress Target Gene Promoters.

Abstract: Translocations of the retinoic acid receptor alpha (RARA) locus with the PLZF or PML genes lead to expression of oncogenic PLZF-RARα or PML-RARα fusion proteins, respectively. These fusion oncoproteins constitutively repress RARα target genes, in large part through aberrant recruitment of multiprotein co-repressor complexes. PML and PML-RARα have previously been shown to associate with the retinoblastoma (Rb) tumour suppressor protein in its hypophosphorylated state. Here we demonstrate that PLZF also interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These two mechanisms are important for maintaining the tight repressive state, which are considered as the major players involved in direct (Beck et al, 2010;Ewing and Kazazian, 2011) DNA interacting proteins, besides PLZF, have been reported to bind to the L1 retrotransposon including Runx3, p53 and SRY associated with the activation of L1 transcription (Tchénio et al, 2000;Yang et al, 2003;Harris et al, 2009). Until now, only one other transcription factor, the retinoblastoma protein (Rb), has been reported to induce L1 transcriptional repression by binding to the L1 promoter (Montoya-Durango et al, 2009) and we have previously shown that Rb and PLZF factors could cooperate to repress specific target promoters (Petrie et al, 2008). In this study, we show that PLZF is able to bind a specific DNA binding site, located outside the L1 promoter, to recruit proteins with epigenetic enzymatic activities (HDAC1 and DNMT1) inducing specific histone deacetylation and DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…These two mechanisms are important for maintaining the tight repressive state, which are considered as the major players involved in direct (Beck et al, 2010;Ewing and Kazazian, 2011) DNA interacting proteins, besides PLZF, have been reported to bind to the L1 retrotransposon including Runx3, p53 and SRY associated with the activation of L1 transcription (Tchénio et al, 2000;Yang et al, 2003;Harris et al, 2009). Until now, only one other transcription factor, the retinoblastoma protein (Rb), has been reported to induce L1 transcriptional repression by binding to the L1 promoter (Montoya-Durango et al, 2009) and we have previously shown that Rb and PLZF factors could cooperate to repress specific target promoters (Petrie et al, 2008). In this study, we show that PLZF is able to bind a specific DNA binding site, located outside the L1 promoter, to recruit proteins with epigenetic enzymatic activities (HDAC1 and DNMT1) inducing specific histone deacetylation and DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…HDACs participate in transcriptional repression of PLZF by deacetylating histones, resulting in local modification of chromatin structure . PLZF physically interacts with HDAC1 , HDAC4 , and Rb for PLZF‐mediated repression. PLZF represses transcription of p53 and decreases p53 protein stability by ubiquitination through corepressor HDACs complex .…”
Section: Gene Regulatory Network Of Plzfmentioning
confidence: 99%
“…ZBTB16 targets these L1 elements by interacting both with the DNA and the L1 RNA, leading to the recruitment of DNMT1 and silencing of L1 retro‐transposition (Puszyk et al, ). Intriguingly, retinoblastoma protein (Rb) also represses L1 elements and it was previously shown that it interacts with ZBTB16 (Petrie et al, ). ZBTB16 regulates the expression of both protein‐coding genes and DNA repeats.…”
Section: Dna Methylation and The Silencing Of Repetitive Elements Andmentioning
confidence: 99%